The Relationship Between Physical Activity and Sleep Duration on The Incidence of Obesity in Children under Five in Central Jakarta and The Review of Islamic Perspective - Astalia Maisya Adhitama; Diniwati Mukhtar; Qomariyah Sachrowardi; Endy Muhammad Istiwara (Junior Medical Journal, 2023)
Introduction: The excessive buildup of fat, known as obesity, can negatively affect health. In 2020, there will be 38.9 million overweight children under the age of five worldwide. 7.8% of toddlers in DKI Jakarta are fat, compared to 7.04% in central Jakarta. A variety of factors cause obesity. The two most important factors are insufficient sleep time and physical exercise. Methodology: This type of research is quantitative with a cross-sectional design. The study population was toddlers in Sawah Besar District, Central Jakarta, a total of 70 people. Results: The results showed that 33 people (47.1%) were ordinary, four people (5.7%) were at risk of being overweight, three people (4.3%) were fat, and 30 people (42.9%) were obese. Moderate physical activity was found in 15 people (50%) normal and 15 people (50%) obese. At the same time, physical activity is less, with as many as 18 people (45%) ordinary and 22 people (55%) obese. Found adequate sleep duration in 21 people (63.648%) were ordinary, and 12 (36.36%) were obese. At the same time, the rest period is seen in as many as 12 people (32.43%) normal and 25 people (67.57%) obese. P=0.810 and p=0.016 show differences in physical activity and sleep duration in obese toddlers. Conclusion: In toddlers in the Sawah Besar District of Central Jakarta, there is a meaningful association between sleep duration and the incidence of obesity (p=0.016) and no relationship between physical activity and the incidence of obesity (p=0.810) with an Odd Ratio value of 1.222.